Is soccer kick performance better after a "faking" (cutting) maneuver task? - Katis, A.; Kellis, E. (Sports Biomechanics, 2011)
Cutting in soccer is a common skill used to avoid the opponent's pressure but the potential effects of such a skill on instep kicking performance have not been previously investigated. The purpose of this study was to examine the differences in lower limb biomechanics between straight approach soccer kicks and kicks performed following a cutting maneuver task. Ten young amateur soccer players performed, in a random order, instep kicks after a two-step straight approach run and kicks after a double "faking" cutting maneuver task. The results showed that kicking after a cutting maneuver task displayed significantly lower ball speed values compared with the straight approach instep kicking (16.73 vs. 19.78 m/s, respectively; p < 0.05). Moreover, analysis of variance showed significant differences between the two kicking conditions in ankle, knee and hip joint displacements. The present study indicated that performing instep kicks after a double-cutting maneuver reduces ball and foot speed probably due to increasing joint frontal and transverse plane rotations. Improvements in the performance of the cutting maneuver task through training might result in better transfer of energy and speed to the kicking task thus permitting players to perform more powerful kicks under realistic game conditions.